Research on the Vocabulary Related to the Social Issues in Khamse of Nezami Based on Fairclough’s Critical Discourse Analysis Approach - Mohammad Irani; Gholamreza Salemian; Zahra Mansouri (Matn/Pizhūhī-i Adabī, 2019)
In discourse, a set of vocabulary words is called a labeled (marked) which has meanings beyond the level of vocabulary. Concentration of choice of such words in poetry is a way toward the facts that have flowed in history. This issue in Nezami’s poem sometimes inapparently places inside marked words which the poet has chosen. In this article, in the way of descriptive – analytic and studying resources related to Nezami’s era history, we consider effective events on the artist’s mind. Then we, with derivation and study of high frequency and marked words in Khamse, proceeded with Significant correlation between the presence of this words in poem and events placed on age of his life. And in order to make a methodical analysis, we chose Fairclough's critical discourse analysis approach. The result showed: The poet's language is a social act, which, while creating its social relationships and identities, is their constructor and a tool for turn to solving odds of power.